The Effectiveness of Long-Term Use of Interactive Media on Learning Achievement and Motivation of Elementary School Students in Rural Indonesia (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to evaluate the longitudinal effectiveness of interactive learning media on academic achievement and learning motivation among elementary school students in rural Indonesia. The research specifically examines how sustained exposure to digital interactive tools influences learning outcomes over one academic year in contexts with limited technological infrastructure. Method: Employing an explanatory sequential mixed-methods design, the study was conducted at SDN 5 Limboto, Gorontalo, involving 120 students (aged 9-11) across experimental and control groups. Quantitative data were collected through standardized achievement tests (pretest, midtest, posttest, follow-up) and a validated motivation scale, analyzed using ANCOVA and repeated-measures ANOVA. Qualitative data from semi-structured interviews with six teachers were analyzed thematically to provide contextual insights. Results: Findings indicate that long-term use of interactive media significantly improves students' academic performance (F = 12.43, p < 0.01, η² = 0.34) and motivation scores (F = 9.82, p < 0.05, η² = 0.29). Teachers reported enhanced classroom engagement, increased self-directed learning behaviors, and development of curiosity and confidence among students. Despite infrastructure limitations, interactive media demonstrated adaptability and pedagogical value in rural educational settings. Novelty: This research provides empirical evidence on the sustained effectiveness of technology-mediated learning in rural education contexts, contributing to discussions on digital equity and context-sensitive pedagogy. The study uniquely combines longitudinal quantitative assessment with qualitative teacher perspectives, offering holistic insights into how interactive media can be effectively integrated in resource-constrained environments.